Does ISO 14001 Moderate the Effect of Green Innovation on Financial Performance - Indira Karima Umaroe; Hamidah Hamidah (Budapest International Research and Critics University, 2022)
The purpose of this research is to gather empirical evidence on the influence of green processes and green product innovation on financial performance moderated by ISO 14001. The research population is the manufacturing sector listed on the Indonesia Stock Exchange during 2012-2019. The sample was chosen based on specific criteria and so the research sample obtained 184 observations. The conclusion is that green process innovation and green product innovation influence an increase in financial performance proxied by return on assets (ROA) however, ISO 14001 certification does not moderate the influence of green process innovation and green product innovation on financial performance. Regardless of whether the organization achieves ISO 14001 certification, it will continue to implement green innovation. The purpose of ISO 14001 certification is to create a green image for the organization; therefore, a company with ISO 14001 certification does not always apply green innovation or even increase its performance.